2014
DOI: 10.1038/ejhg.2014.85
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex IV deficiency, caused by mutated COX6B1, is associated with encephalomyopathy, hydrocephalus and cardiomyopathy

Abstract: Isolated cytochrome c oxidase (COX) deficiency is a prevalent cause of mitochondrial disease and is mostly caused by nuclear-encoded mutations in assembly factors while rarely by mutations in structural subunits. We hereby report a case of isolated COX deficiency manifesting with encephalomyopathy, hydrocephalus and hypertropic cardiomyopathy due to a missense p.R20C mutation in the COX6B1 gene, which encodes an integral, nuclear-encoded COX subunit. This novel mutation was predicted to be severe in silico. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 21 publications
4
62
0
Order By: Relevance
“…7A). Remarkably, previous studies had evidenced that resveratrol, an anti-oxidant metabolite, improves complex IV activity [43], thus strengthening our results. In addition, Blue Native (BN)-PAGE analyses of digitonin-solubilized adipocyte mitochondria revealed that complex IV was found significantly decreased in diabetic compared to non-diabetic patients (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…7A). Remarkably, previous studies had evidenced that resveratrol, an anti-oxidant metabolite, improves complex IV activity [43], thus strengthening our results. In addition, Blue Native (BN)-PAGE analyses of digitonin-solubilized adipocyte mitochondria revealed that complex IV was found significantly decreased in diabetic compared to non-diabetic patients (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The occurrence of shared features between aging and T2DM explains that 37% of DAPs were found common to the two comparisons. Thus, cytochrome c oxidase subunit 6B1 (COX6B1), a key player in cytochrome c oxidase activity [43], [44], was found down-regulated in the age (Zq=−2.75) and T2DM (Zq=−5.06) comparisons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Finally, mutations in CIII and CIV have been shown to result in human patients with cardiomyopathy. 5255 …”
Section: Building the Mitochondrion: Genomic Assembly And Maintenancementioning
confidence: 99%
“…For diagnostic testing, cultured skin fibroblasts are an attractive tissue to evaluate OXPHOS function because of the minimally invasive character of sampling and the amount of cell material obtained by culturing [7]. Studies in human COX-deficient fibroblasts, derived from patients, have revealed diminished COX activity, compromised ATP production, reactive oxygen species (ROS) overproduction and abnormal mitochondrial morphology [810]. …”
Section: Introductionmentioning
confidence: 99%